Migration and maternity: Insights of context, health policy, and research evidence on experiences and outcomes from a three country preliminary study across Germany, Canada, and the United Kingdom - Higginbottom, Gina; Reime, Birgit; Kuldip, Bharj; Chowbey, Punita; Ertan, Kubilay; Foster-Boucher, Caroline; Friedrich, Jule; Gerrish, Kate; Kentenich, Heribert; Mumtaz, Zubia; O'Brien, Beverley; Salway, Sarah (My University, 2013)
A group from Germany, Canada, and the United Kingdom undertook country-specific scoping reviews and stakeholder consultations before joining to holistically compare migration and maternity in all three countries. We examined four interlinking dimensions to understand how international migrant/minority maternal health might be improved upon using transnational research: (a) wider sociopolitical context, (b) health policy arena, (c) constellation, outcomes, and experiences of maternity services, and (d) existing research contexts. There was clear evidence that the constellation and delivery of services may undermine good experiences and outcomes. Interventions to improve access and quality of care remain small scale, short term, and lacking in rigorous evaluation.
Keywords: health of mothers; maternal health; emigration and immigration; health policy